Headaches and family planning: insights from a Japanese school-based survey - Masahito Katsuki; Naomichi Wada; Keiko Iijima; Noriyuki Yoshizawa; Yoshizumi Toya; Yasuko Hanaoka; Kazuma Kaneko; Shoji Kajikawa (The Journal of Headache and Pain)
Abstract Objective To investigate the effect of headaches on women’s pregnancy plans and fertility intentions. Methods We prospectively performed a school-based online survey for students’ parents in Suwa city, Japan, in 2023. We asked their age, sex, the number of children, the presence of headache attacks, the use of acute and prophylactic medications, monthly headache days (MHD), monthly acute medication intake days (AMD), headache impact test-6 (HIT-6), and whether or not headaches worsen during menstruation. We also examined headache’s effect on pregnancy plans and asked about how headaches would affect pregnancy, the ability to raise a child, and the child’s health.Of 5558 students' households, we retrieved 1142 (20.1%) answers, and 717 (12.9%) responses from parents with headaches. Results Of 5558 students’ households, we retrieved 1142 (20.1%) answers, and 717 (12.9%) responses from parents with headaches were finally analyzed. The median (first quartile-third quartile) age was 43 (37–46) years, and 653 (91.1%) were female. Median MHD, AMD, and HIT-6 were 3 (1–6), 3 (1.5-6), and 62 (58–65), respectively. Twenty-four (3.3%) used prophylactic medications and 562 (78.4%) used acute medications for headache attacks. The median number of children was 2 (1–2). Avoid pregnancy group consisted of 39/717 (5.4%) respondents. They were younger (median 39 years; first quartile-third quartile 33–42 years), with more respondents with headaches worsening during menstruation (28/35; 80.0%), with acute medication use (36/39; 92.3%), and had more MHD (5; 3–10), more AMD (5; 2–11), and high HIT-6 score (66; 60–67), compared to the no impact group. They tended to think that headaches would be worse during pregnancy (16/39; 41.0%) and that headaches negatively affect pregnancy (28/39; 71.8%), raising a child (20/39; 51.3%), and the child’s development (31/39; 79.5%) and risk of having a headache (28/39; 71.8%) compared to the no impact group. Conclusions Some of the respondents avoided pregnancy because of their headaches. Those in avoid pregnancy group had severe headaches and felt that headaches negatively affected family planning.